BAT1, a putative acyltransferase, modulates brassinosteroid levels in Arabidopsis. (31st December 2012) - Choi, Sunhwa; Cho, Young‐hyun; Kim, Kangmin; Matsui, Minami; Son, Seung‐Hyun; Kim, Seong‐Ki; Fujioka, Shozo; Hwang, Ildoo
Summary Brassinosteroids (BRs) are essential for various aspects of plant development. Cellular BR homeostasis is critical for proper growth and development of plants; however, its regulatory mechanism remains largely unknown. BAT1 (BR‐related acyltransferase 1), a gene encoding a putative acyltransferase, was found to be involved in vascular bundle development in a full‐length cDNA over‐expressor (FOX) screen. Over‐expression of BAT1 resulted in typical BR‐deficient phenotypes, which were rescued by exogenously applied castasterone and brassinolide. Analyses of BR profiles demonstrated that BAT1 alters levels of several brassinolide biosynthetic intermediates, including 6‐deoxotyphasterol, typhasterol and 6‐deoxocastasterone. BAT1 is mainly localized in the endoplasmic reticulum. BAT1 is highly expressed in young tissues and vascular bundles, and its expression is induced by auxin. These data suggest that BAT1 is involved in BR homeostasis, probably by conversion of brassinolide intermediates into acylated BR conjugates.